Optimasi Sifat Biofiber Sisal Melalui Modifikasi Dengan Impregnasi Dan Asam Stearat Untuk Aplikasi Biokomposit - Desiasni, Rita; Izzati, Nurul; ., Sukarsih; Riski, Muhammad (Rekayasa Material, Manufaktur dan Energi, 2025)
This research aims to optimize the properties of biofiber made from sisal fiber through modification with stearic acid. Sisal fiber is known to have high potential as a natural raw material, but its mechanical properties still need to be improved for wider industrial applications. The modification process is carried out by soaking the sisal fiber in a stearic acid solution with varying concentrations.  Laboratory tests were carried out to evaluate the effectiveness of modifying the physical properties of sisal biofiber in the form of 1 cm short fiber fibers and 200 mesh sisal powder to determine the most effective modification between the two fiber sizes. Based on the results obtained, the highest cellulose, namely 64.7%, was obtained from the results of impregnation of the fiber. The lignin content decreased in impregnated sisal fiber to 9.2% from 12.48% without treatment. The results of NDF which produce cellulose and lignin levels are strengthened by SEM results on 4% sisal fiber. These results show that the sisal fiber without stearic acid treatment shows a greater distribution of lignin compared to the sisal fiber treated with 4% stearic acid.